The Role of Creative Economy Actors in Integrating Islamic Economic Values into Products and Design - Yulada Syurfa; Syamsuddin Syamsuddin; Uthman Shehu Lawal (Journal of Management, Finance, and Accounting Research, 2026)
The batik industry has experienced significant growth. However, there are still issues within the batik industry that require attention. The aims of this study is to examine how Islamic values can be integrated to enhance the creative economy through the batik industry, covering the production process, product design, as well as product distribution and marketing. In addition, this study includes an analysis of the potential of the batik industry in the global halal market. The method used in this research is a qualitative approach. The findings indicate that the integration of Islamic values has been implemented through the application of Islamic economic principles in the production process, including the use of halal raw materials, a fair wage system, and a commitment to environmental sustainability. Avoiding inappropriate motifs and not copying other people's work are two ways that Islamic economic values are put into practice in product design. Meanwhile, transparency and honesty demonstrate the implementation of Islamic economic values in product distribution and marketing. Indonesian batik has strong potential in the global halal fashion market due to rising global interest, a growing Muslim population, increased purchasing power, and supportive halal certification policies. [Industri batik telah mengalami pertumbuhan yang signifikan.  Namun, masih ada masalah dalam industri batik yang memerlukan perhatian. Tujuan penelitian ini yaitu untuk mengetahui bagaimana nilai-nilai Islam dapat diintegrasikan dalam rangka peningkatan ekonomi kreatif melalui industri batik mulai dari proses produksi, desain produk, hingga distribusi dan pemasaran produk. Selain itu, penelitian ini menambahkan analisis potensi industri batik dalam pasar halal global. Metode yang digunakan pada penelitian ini adalah metode kualitatif. Hasil penelitian menunjukkan bahwa integrasi nilai-nilai Islam telah dilakukan melalui implementasi nilai ekonomi islam dalam proses produksi yaitu penggunaan bahan baku yang halal, sistem upah yang adil, dan komitmen terhadap pelestarian lingkungan. Implementasi nilai ekonomi islam dalamdesain produk ditunjukkan dengan menghindari motif yang tidak pantas dan tidak menjiplak karya orang lain. Implementasi nilai ekonomi islam dalam distribusi dan pemasaran produk tercermin melalui transparansi dan kejujuran. Batik Indonesia memiliki potensi besar di pasar fashion halal global karena meningkatnya minat global, pertumbuhan populasi Muslim, daya beli yang meningkat, serta kebijakan sertifikasi halal yang mendukung]